PENGARUH AUDIT TENURE, AUDIT FEE, ROTASI AUDITOR, SPESIALSIASI AUDITOR, DAN UMUR PUBLIKASI PADA KUALITAS AUDIT - Pramaswaradana, I Gusti Ngurah Indra; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
This study aim to provide empirical evidence about the effect of audit tenure, audit fee, auditor rotation, auditor specialization, and age of publication on audit quality. The population in this study is all of manufacturing company listed in Indonesia Stock Exchange on period 2013-2015. The sampling method used the method of purposive sampling with the result 67 company sample. Data collection method used the method of non participant observation with download data from official webside Indonesia stock exchange. Data analysis used the technique of logistic regression. The result of hypothesis is audit tenure had negative effect on audit quality, audit fee had positive effect on audit quality, while rotation, specialization, and age of publication had no effect on audit quality.
Keywords: audit tenure, audit fee, auditor rotation, auditor specialization, age of publication, audit quality.